The Automatic Onion Cutter Using Arduino Uno as Control System Tool - Putra Jaya; Hendra Hidayat; Delsina Faiza; Almasri Almasri; Zulwisli Zulwisli; Muhammad Aidil (Universitas Negeri Padang, 2022)
Today's technological developments are growing rapidly, but there are still jobs that are done manually and semi-manually. This paper aims to develop a control system to coordinate the work of tools using an electric motor, which is very helpful in the process of cutting onions in large quantities and is more efficient in spending production costs because the tool designed is an automatic onion cutter. This research method begins with the collection of materials and data related to onion cutters, production of onion cutters, and testing of onion cutters. The measurement results of the tool show that every component in the automatic onion cutter works well and optimally; the measurement process is carried out properly and thoroughly. This optimal work result is supported by Arduino Uno. The Arduino Uno microcontroller acts as a tool controller. In the main system, the onion cutter is controlled by the Arduino Uno with the Arduino programming language. This automatic onion cutting system will work when the onion you want to cut has been inserted into a cross-section that has been equipped with an ultrasonic sensor, and then the onion cutting process is carried out. Compared with the manual method, the cutting time is almost the same. It's just that the advantages of slicing with this tool, the resulting slices are relatively more uniform. Besides that, another advantage is that it doesn't hurt the eyes of the onion slicer. So that this tool can be used by small entrepreneurs and onion farmers to increase productivity and the community's economy.